A closer look at mineral aerosol emissions from the Makgadikgadi Pans, Botswana, using automated SEM-EDS (QEMSCAN®). Issue 1 (5th January 2021) - Vickery, Kathryn; Eckardt, Frank
ABSTRACT: This paper demonstrates the use of Quantitative Evaluation of Minerals by SCANning electron microscopy (QEMSCAN®), an automated scanning microscopy technique, which combines scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), providing ultra-fast analysis of particle grains at a micron-scale resolution. We evaluate its application in aerosol studies by comparing surface and airborne samples from the Makgadikgadi Pan in Botswana. The playa is a major global dust emitter and its aerosols have a widespread effect on atmospheric, biological and terrestrial processes. Sampling was conducted at a carefully selected surface location and associated BSNE dust trap stack at 0.25, 0.5, 0.85 1.65 meters. The dominant minerals identified here are quartz, halite, thernadite, mica, calcite and feldspar. Surface sample results from QEMSCAN are in line with other forms of elemental and mineralogical analyses. When comparing surface samples with elevated trap samples, we noted a fining and fractionation during grain entrainment, resulting in a compositional shift with height. We also observed some ultra-fine fraction losses from the BSNE traps. Overall, the single location here establishes the link between fluvial playa basin inputs, sediment storage, evaporation products and aeolian losses and outputs from a dry lake surface, not unlike semi-arid evaporative dust sources elsewhere.